The role and behaviour of mitochondrial creatine kinase in hepatocellular carcinoma and its potential use as a tumor detecting biomarker for cancer patients - Siyahmazgi, Ali Nemati; Mazar, Mina Ghorbani; Vakilinia, Maede; Javid, Hossein (International Journal of Scientific Reports, 2023)
Hepatocellular carcinoma (HCC) is responsible for approximately 75% of all liver cancer cases, which is the seventh most prevalent cancer and the second most common cause of cancer mortality worldwide. The prognosis of HCC depends on its stage and the severity of liver disease at the time of diagnosis, but there are still problems in detecting and treating HCC patients on time and effectively. Being unable to diagnose HCC patients at an early stage and ineffective therapies for HCC patients with advanced stages are associated with the disease’s high mortality. Liver transplantation could be a treatment option If patients are diagnosed early, but unfortunately, most patients are diagnosed at an advanced stage where chemotherapy is necessary. Thus, an effective strategy for early detection of HCC is necessary since there was no effective chemotherapy for advanced HCC for a long time, and therapies such as the anti-angiogenesis pathway can only extend the median survival from 7.9 months to 10.7 months which is a step forward but not enough. In this article, we review the role of MtCK in HCC and its potential use as a marker to see if using it can be beneficial to patients.